Raw Milk Composition of Crossbred Cows and Correlation Between Milk Constituents in Selected Districts of Chhattisgarh, India - Chandrakar, Choodamani; Kumar, Praveen; Shakya, Sanjay; Jaiswal, Sudhir Kumar; Monika; Wasist, Upendra (International Journal of Bio-resource and Stress Management, 2017)
The present study was carried out in four districts of Chhttisgarh to determine the quality of raw milk in this region. A total of 92 milk sample from crossbred cattle was collected and analysied for physico-chemical properties. The ANOVA analysis revealed that there is a significant difference (p<0.05) in all physico-chemical parameters among the districts, difference was non-significant in case of lactose percentage and Density. The overall mean percentages of fat, solid non-fat (SNF) and protein obtained were 3.812±0.043, 8.444±0.048 and 3.412±0.036 in that order. Durg districts recorded highest fat and snf content in comparisons to other district of study. In this study, highly significant (p<0.01) positive correlation was observed between fat and SNF (0.792), fat and protein (0.330) and fat and lactose (0.482). Correlation between SNF with protein (0.333) and lactose (0.345) were found to be positive and highly significant (p<0.01).Density showing non-significant correlation with all the milk constituent parameters. Efforts should be taken to change nutritionand management aspects in such a manner that quality parameter of milk is improved.Values of genetic correlations between productions have huge importance in selection of cows, as they provide possibility for selection of heads on more traits at the same time.